Human IgM–expressing memory B cells - Budeus, Bettina; Kibler, Artur; Küppers, Ralf (Frontiers in Immunology, 2023)
A hallmark of T cell dependent (TD) humoral immune responses is the generation of long-lived memory B cells. The generation of these cells occurs primarily in the germinal center (GC) reaction, where antigen-activated B cells undergo affinity maturation as a major consequence of the combined processes of proliferation, somatic hypermutation of their immunoglobulin V (IgV) region genes, and selection for improved affinity of their B-cell antigen receptors. As many B cells also undergo class-switching to IgG or IgA in these TD responses, there was traditionally a focus on class-switched memory B cells in both murine and human studies on memory B cells. However, it has become clear that there is also a large subset of IgMexpressing memory B cells, which have important phenotypic and functional similarities but also differences to class-switched memory B cells. There is an ongoing discussion about the origin of distinct subsets of human IgM + B cells with somatically mutated IgV genes. We argue here that the vast majority of human IgM-expressing B cells with somatically mutated IgV genes in adults is indeed derived from GC reactions, even though a generation of some mostly lowly mutated IgM + B cells from other differentiation pathways, mainly in early life, may exist.